论《蹲向传统或坐看现代》的翻译策略及其意义 = The translation techniques and purposes of Squat for Tradition, Sit for Modernity - 梁玉倩 Niyu, Yuqian (Nanyang Technological University, 2025)
新华文学翻译的研究不多，因为新加坡翻译文学仍然处在萌芽阶段。本文探讨的是新华文学翻译的意义所在，所选的研究对象的谢裕民的《蹲向传统或坐看现代》，以及它的英译本Squat for Tradition, Sit for Modernity。研究表明，译者陈丹枫运用了许多翻译手法，以便达到译文增加传播量的目的。由此可见，翻译的目的不仅仅是译者、翻译发起人或翻译赞助人制定的，更是新加坡这个大环境的多元系统制定的。新华文学翻译的意义包括教育意义和文化意义，旨在提升弱势文化的传承。 Studies of the translation of Singapore Chinese literary works were limited as we had just started translating the literary works of Singapore. This study aims to find out the purpose of translating Singapore Chinese Literature and has chosen the case study of Chia Joo Ming’s Squat for Tradition, Sit for Modernity and its Chinese original. Findings show that the translator, Tan Dan Feng used a variety of translation techniques to fulfil the purpose of spreading the work. This shows that what decides the purpose of translation is not just the translator, the initiator or the patronage. It is the polysystem of the environment in Singapore that decides said purpose. The purpose of translating Singapore Chinese Literature is both educational and cultural, to increase the popularity and the passing down of a weaker culture.